Increased hexosamine biosynthetic pathway flux impairs myocardial GLUT4 translocation - Williams, Gordon (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Physiological Sciences))--University of Stellenbosch, 2009.